Pole-skipping of scalar and vector fields in hyperbolic space: conformal blocks and holography - Yongjun Ahn; Viktor Jahnke; Hyun-Sik Jeong; Keun-Young Kim; Kyung-Sun Lee; Mitsuhiro Nishida (Journal of High Energy Physics, 2020)
Abstract Motivated by the recent connection between pole-skipping phenomena of two point functions and four point out-of-time-order correlators (OTOCs), we study the pole structure of thermal two-point functions in d-dimensional conformal field theories (CFTs) in hyperbolic space. We derive the pole-skipping points of two-point functions of scalar and vector fields by three methods (one field theoretic and two holographic methods) and confirm that they agree. We show that the leading pole-skipping point of two point functions is related with the late time behavior of conformal blocks and shadow conformal blocks in four-point OTOCs.